تقييم كفاءة توزيع مراكز الدفاع المدني في المراكز الحضرية لمحافظة واسط - ضاري عطا الله عبد الجليل (Journal of College of Education, 2019)
The study evaluates the efficiency of the distribution of civil defense centers in urban areas in Wasit province. Three local criteria related to the Ministry of Construction and Housing are applied to find out its relevance to the population and the measurement of each city in the province. The first criterion is represented by the size of population and is specified on the basis that each civil defense center must provide its services for (12000) people. The second criterion is represented by the mileage which is specified by (1200) meters for each civil defense center, while the third criterion is represented by the response time specified by (10) minutes according to the local criterion and (4) minutes according to the global one. Through this evaluation, the need to build up additional civil defense centers is identified in a way fits the population of cities and their measurements.